2022
DOI: 10.1186/s13287-022-02743-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and mechanism of mesenchymal stromal cells in treatment of COVID-19

Abstract: Coronavirus disease 2019 (COVID-19) is a highly infectious epidemic disease that has seriously affected human health worldwide. To date, however, there is still no definitive drug for the treatment of COVID-19. Cell-based therapies could represent a new breakthrough. Over the past several decades, mesenchymal stromal cells (MSCs) have proven to be ideal candidates for the treatment of many viral infectious diseases due to their immunomodulatory and tissue repair or regeneration promoting properties, and severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…A smaller but growing number of phase 2 efficacy trials have demonstrated efficacy in some cases but not in others. The most extensive experience to date is in investigations of systemic MSC administration in patients with either non-COVID or COVID19-related ARDS with recent meta-analyses of COVID-19 related-ARDS demonstrating significant benefits of MSC administration ( Khoury et al, 2020 ; Qu et al, 2020 ; Zhu et al, 2021 ; Kirkham et al, 2022 ; Lu et al, 2022 ). Intensive deliberation about the varying outcomes in these trials has highlighted ongoing issues with investigations of MSC administration not just in patients with respiratory diseases or critical illnesses but in a wider range of conditions.…”
Section: Overview Of Lung Regenerative Medicinementioning
confidence: 99%
“…A smaller but growing number of phase 2 efficacy trials have demonstrated efficacy in some cases but not in others. The most extensive experience to date is in investigations of systemic MSC administration in patients with either non-COVID or COVID19-related ARDS with recent meta-analyses of COVID-19 related-ARDS demonstrating significant benefits of MSC administration ( Khoury et al, 2020 ; Qu et al, 2020 ; Zhu et al, 2021 ; Kirkham et al, 2022 ; Lu et al, 2022 ). Intensive deliberation about the varying outcomes in these trials has highlighted ongoing issues with investigations of MSC administration not just in patients with respiratory diseases or critical illnesses but in a wider range of conditions.…”
Section: Overview Of Lung Regenerative Medicinementioning
confidence: 99%
“…For instance, they can inhibit the abnormal activation and overproliferation of T-helper 1 (Th1) cells by regulating the NKG2D signaling pathways to modulate the Th1/Th2 balance. [165,166] Moreover, miRNAs in MSC-EVs, such as miR-27a-3p, miRNA Let-7, and miR-100, are able to promote macrophage polarization from the proinflammatory M1 type to the anti-inflammatory M2 type. [153,167,168] In addition to mammalian cells and their EVs, some edible plant-derived biomaterials also contain exosome-like nanoparticles (ELNs) with anti-inflammatory and drug-delivery functions.…”
Section: Anti-inflammationmentioning
confidence: 99%
“…For instance, they can inhibit the abnormal activation and overproliferation of T‐helper 1 (Th1) cells by regulating the NKG2D signaling pathways to modulate the Th1/Th2 balance. [ 165,166 ] Moreover, miRNAs in MSC‐EVs, such as miR‐27a‐3p, miRNA Let‐7, and miR‐100, are able to promote macrophage polarization from the proinflammatory M1 type to the anti‐inflammatory M2 type. [ 153,167,168 ]…”
Section: Applications Of Cell‐based Biomaterials In Coronavirus Disea...mentioning
confidence: 99%
“…A report of the first compassionate use of MSCs in a Chinese patient with severe SARS-CoV-2 infection was published in January 2019 [ 13 , 14 ]. The promising results of this study have led to many clinical trials evaluating one or repeated infusions of MSCs themselves under the status of advanced therapy drugs [ 14 , 15 , 16 ] or using MSCs as raw material for extracellular vesicle (EV) production [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%